Deoxygenation enhances photosynthetic performance and increases N2 fixation in the marine cyanobacterium Trichodesmium under elevated pCO2 - Li, He; Gao, Kunshan (Frontiers in Microbiology, 2023)
Effects of changed levels of dissolved O2 and CO2 on marine primary producers are of general concern with respect to ecological effects of ongoing ocean deoxygenation and acidification as well as upwelled seawaters. We investigated the response of the diazotroph Trichodesmium erythraeum IMS 101 after it had acclimated to lowered pO2 (~60 μM O2) and/or elevated pCO2 levels (HC, ~32 μM CO2) for about 20 generations. Our results showed that reduced O2 levels decreased mitochondrial respiration and photorespiration significantly, and increased the net photosynthetic rate by 66% and 89% under the ambient (AC, ~13 μM CO2) and the HC, respectively. The reduced pO2 enhanced the N2 fixation rate by ~139% under AC and only by 44% under HC, respectively. The N2 fixation quotient, the ratio of N2 fixed per O2 evolved, increased by 143% when pO2 decreased by 75% under the elevated pCO2. Meanwhile, particulate organic carbon and nitrogen production rates increased simultaneously under reduced O2 levels, regardless of the pCO2 treatments. Nevertheless, changed levels of O2 and CO2 did not bring about significant changes in the specific growth rate of the diazotroph. Such inconsistency was attributed to the daytime positive and nighttime negative effects of both lowered pO2 and elevated pCO2 on the energy supply for growth. Our results suggest that Trichodesmium decrease its mitochondrial respiration by 5% and increase its N2-fixation by 49% and N2-fixation quotient by 30% under future ocean deoxygenation and acidification with 16% decline of pO2 and 138% rise of pCO2 by the end of this century.